What Is the Appropriate Reference for Evaluating the Recovery of Supraspinatus Muscle Atrophy After Arthroscopic Rotator Cuff Repair? The Occupation Ratio of the Supraspinatus May Change After Rotator Cuff Repair Without Volumetric Improvement. Issue 6 (May 2018) - Sasaki, Tsuyoshi; Shitara, Hitoshi; Yamamoto, Atsushi; Hamano, Noritaka; Ichinose, Tsuyoshi; Shimoyama, Daisuke; Kobayashi, Tsutomu; Osawa, Toshihisa; Tsushima, Yoshito; Takagishi, Kenji; Chikuda, Hirotaka
Background: Supraspinatus muscle atrophy is typically assessed by the occupation ratio of the cross-sectional area of the muscle belly to the supraspinatus fossa at the medial border of the coracoid process in a slice along the oblique-sagittal plane on MRI. Previous studies have shown that the occupation ratio of the supraspinatus changed soon after rotator cuff repair compared with before surgery. However, no studies have examined the perioperative change in the muscle volume assessed with 3-dimensional measurement. Purpose: To compare the volume of the supraspinatus muscle before and soon after surgery by using 3-dimensional imaging and to elucidate whether the changes in the occupation ratio represent corresponding changes in the muscle volume. Study Design: Cohort study; Level of evidence, 3. Methods: Thirty shoulders of patients who underwent arthroscopic rotator cuff repair were evaluated. T2-weighted images were obtained before surgery and 2 weeks after surgery. After the muscle and its tendon borders were plotted, the supraspinatus and its tendon were segmented with interactive thresholding in all slices. The 3-dimensional images were then reconstructed and the volumes calculated. Changes in the muscle volume and the occupation ratio were evaluated via 3-dimensional and 2-dimensional image assessments. The 3-dimensional and 2-dimensional findings before and after surgery were compared by use of paired t tests. Results: The mean muscle volume did not change significantly at a time point soon after surgery in any group. In patients with little medial retraction (n = 7) or isolated detachment at the superior facet (n = 17), no significant differences were noted in the occupation ratio after surgery compared with before surgery. In contrast, in patients with moderate medial retraction (n = 23) or extended tearing in the transverse direction (n = 13), the occupation ratio increased significantly. Conclusion: Although the muscle volume did not change soon after surgery compared with the preoperative values, in patients with moderate medial retraction or extended tearing in the transverse direction, the occupation ratio increased, probably due to lateral traction of the supraspinatus muscle. We recommend that MRI findings obtained soon after surgery be used as the time-zero reference for evaluating the postoperative changes in the supraspinatus.